Measuring mitochondrial respiration in intact single muscle fibers - Schuh, Rosemary A. (American Physiological Society, 2012)
Measurement of mitochondrial function in skeletal muscle is a vital tool for understanding regulation of cellular bioenergetics. Currently, a number of different experimental approaches are employed to quantify mitochondrial function, with each involving either mechanically or chemically induced disruption of cellular membranes. Here, we describe a novel approach that allows for the quantification of substrate-induced mitochondria-driven oxygen consumption in intact single skeletal muscle fibers isolated from adult mice. Specifically, we isolated intact muscle fibers from the flexor digitorum brevis muscle and placed the fibers in culture conditions overnight. We then quantified oxygen consumption rates using a highly sensitive microplate format. Peak oxygen consumption rates were significantly increased by 3.4-fold and 2.9-fold by simultaneous stimulation with the uncoupling agent, carbonyl cyanide p-(trifluoromethoxy)phenylhydrazone (FCCP), and/or pyruvate or palmitate exposure, respectively. However, when calculating the total oxygen consumed over the entire treatment, palmitate exposure resulted in significantly more oxygen consumption compared with pyruvate. Further, as proof of principle for the procedure, we isolated fibers from the mdx mouse model, which has known mitochondrial deficits. We found significant reductions in initial and peak oxygen consumption of 51% and 61% compared with fibers isolated from the wild-type (WT) animals, respectively. In addition, we determined that fibers isolated from mdx mice exhibited less total oxygen consumption in response to the FCCP + pyruvate stimulation compared with the WT mice. This novel approach allows the user to make mitochondria-specific measures in a nondisrupted muscle fiber that has been isolated from a whole muscle.